The Effect of Current Ratio, Debt-to-Equity Ratio, and Return on Assets on Stock Prices of Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) 2022-2024 - Fianiningsi Fianiningsi; Nasrullah Nasrullah; Sahabuddin Sahabuddin (Journal Social Society, 2026)
This study examines the effect of the Current Ratio (CR), Debt-to-Equity Ratio (DER), and Return on Assets (ROA) on the stock prices of food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Using a quantitative approach and multiple linear regression analysis, the study analyzed 32 companies selected through purposive sampling from a population of 68 firms. The results indicate that all three financial ratios have a significant effect on stock prices. Partially, the Current Ratio significantly influences stock prices (p = 0.001), suggesting that a stronger liquidity position increases investor confidence. Return on Assets also has a significant effect (p = 0.002), indicating that higher profitability contributes positively to stock valuation. Likewise, the Debt-to-Equity Ratio significantly affects stock prices (p = 0.004), reflecting the importance of capital structure in investors’ assessments. Simultaneously, CR, DER, and ROA jointly have a significant effect on stock prices (p = 0.030), demonstrating that liquidity, profitability, and leverage collectively influence market valuation. These findings provide empirical evidence that financial performance indicators play an important role in determining stock prices in the food and beverage sector. The study offers practical implications for investors in evaluating investment opportunities and for corporate managers in improving financial performance to enhance firm value. Overall, maintaining sound liquidity, profitability, and capital structure is essential for supporting favorable stock price performance and attracting investor interest in the capital market.